A Systematic Review of Automatic Health Monitoring in Calves: Glimpsing the Future From Current Practice - Sun, Dengsheng; Webb, Laura; van der Tol, P. P. J.; van Reenen, Kees (Frontiers in Veterinary Science, 2021)
Infectious diseases particularly bovine respiratory disease (BRD) and neonatal calf diarrhea (NCD) are prevalent in calves. Efficient health monitoring tools to identify such diseases on time are lacking. Common practice (i.e. health checks) often identifies sick calves at a late stage of disease or not at all. Sensor technology enables the automatic and continuous monitoring of calf physiology or behavior, potentially offering timely and precise detection of sick calves. A systematic overview of automated disease detection in calves is still lacking. The objectives of this literature review were hence: 1) to investigate previously applied sensor validation methods used in the context of calf health, 2) to identify sensors used on calves, the parameters these sensors monitor, and the statistical tools applied to identify diseases, 3) to explore potential research gaps and to point to future research opportunities. To achieve these objectives, systematic literature searches were conducted. We defined four stages in the development of health monitoring systems: 1) sensor technique, 2) data interpretation, 3) information integration, and 4) decision support. Fifty-five articles were included (stage one: 27, stage two: 19, stage three: 9, and stage four: 0). Common parameters that assess the performance of these systems are sensitivity, specificity, accuracy, precision, and negative predictive value. Gold standards that typically assess these parameters include manual measurement and manual health assessment protocols. At stage one, automatic feeding stations, accelerometers, infrared thermography cameras, microphones, and 3-D cameras are accurate in screening behavior and physiology in calves. At stage two, changes in feeding behaviors, lying, activity, or body temperature corresponded to changes in health status, and point to health issues earlier than manual health checks. At stage three, accelerometers, thermometers, and automatic feeding stations have been integrated into one system which was shown to be able to successfully detect diseases in calves, including BRD and NCD. We discuss these findings, look into potentials at stage four and touch upon the topic of resilience, whereby health monitoring system might be used to detect low resilience (i.e. prone to disease but clinically healthy calves), promoting further improvements in calf health and welfare.